2009
DOI: 10.4103/0250-474x.51957
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of salbutamol sulphate and bromhexine hydrochloride in tablets by reverse phase liquid chromatography

Abstract: A simple reverse phase liquid chromatographic method has been developed and subsequently validated for simultaneous determination of salbutamol sulphate and bromhexine hydrochloride. The separation was carried out using a mobile phase consisting of acetonitrile, methanol and phosphate buffer, pH 4 in the ratio 60:20:20 v/v. The column used was SS Wakosil-II C-18 with a flow rate of 1 ml/min and UV detection at 224 nm. The described method was linear over a concentration range of 10-110 μg/ml and 20-140 μg/ml f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 1 publication
0
8
0
3
Order By: Relevance
“…Several analytical methods for the determination of salbutamol were developed and reported such as TLC (Dave et al, 2011), GC and GC-MS (Caban et al, 2011;Wang et al, 2010), cyclic voltammetry (Ganjali et al, 2005, adsorptive stripping voltammetry on a carbon paste electrode (Attaran et al, 2012), Capillary electrophoresis coupled with electrochemilumencesis (Bao et al, 2012), flow injection method (Al-Abachi and Subhi, 2013), HPLC and RP-HPLC (Mukesh and Ranjit, 2011;Pai et al, 2009 ;Ghulam et al, 2009 ;Li et al, 2010), HPLC-chemiluminescence (Zhang et al, 2011), solid phase extraction (SPE)-HPLC (Liu and Wang , 2011;Yan et al, 2012) , and fluorescence (Tang et al, 2010).…”
Section: Salbutamol Sulphatementioning
confidence: 99%
“…Several analytical methods for the determination of salbutamol were developed and reported such as TLC (Dave et al, 2011), GC and GC-MS (Caban et al, 2011;Wang et al, 2010), cyclic voltammetry (Ganjali et al, 2005, adsorptive stripping voltammetry on a carbon paste electrode (Attaran et al, 2012), Capillary electrophoresis coupled with electrochemilumencesis (Bao et al, 2012), flow injection method (Al-Abachi and Subhi, 2013), HPLC and RP-HPLC (Mukesh and Ranjit, 2011;Pai et al, 2009 ;Ghulam et al, 2009 ;Li et al, 2010), HPLC-chemiluminescence (Zhang et al, 2011), solid phase extraction (SPE)-HPLC (Liu and Wang , 2011;Yan et al, 2012) , and fluorescence (Tang et al, 2010).…”
Section: Salbutamol Sulphatementioning
confidence: 99%
“…[4] Several methods have been reported spectrophotometry, [5][6][7] high-performance liquid chromatography (HPLC). [8][9][10][11][12][13][14] Cephalexin [ Figure 1] is chemically {(6R, 7R)-7-[(R)-2-amino-2-phenylacetamido]-3-methyl-8-oxo-5-thia-1-azabicyclo [4.2.0] oct-2-ene-2-carboxylic acid monohydrate} [15] which is a first-generation cephalosporins for oral administration which is bactericidal and mainly used in the treatment of various bacterial infections caused by Grampositive and Gram-negative microorganisms. [16] Cephalexin is official in IP, [17] United States Pharmacopoeia, [18] and BP.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the reported methods for racemic salbutamol sulfate includes titrimetric (Basavaiah et al, 2006(Basavaiah et al, , 2007, potentiometric (Abdel-Ghani et al, 2002), spectrophotometric (Basavaiah et al, 2003(Basavaiah et al, , 2006(Basavaiah et al, , 2007Chitlange et al, 2011;Culzoni et al, 2006; Geeta et al ., 1989;Habib et al, 2004;Jain et al, 2011;Mishra et al, 2010;Parimoo et al, 1993;Rathore et al, 1993), spectrofluorimetric (Pandya et al, 2010), HPLC (Bernal et al, 1996;Boulton et al, 1995;Chitlange et al, 2011;Erram et al, 2006;Jain et al, 2011;Kasawar et al, 2010;Kountourellis et al, 1990;Martis et al, 2011;Murtaza et al, 2009;Pai et al, 2009) and LC-MS (Joyce et al, 1998;Wu et al, 2004Wu et al, , 2011Yee et al, 2011). Whereas for levosalbutamol sulfate a few spectrophotometric Thulasama et al, 2009) and HPLC (Ghemud et al, 2012;Halabi et al, 2004; methods are reported.…”
Section: Introductionmentioning
confidence: 99%